On the singular spectrum of radiation operators in the non-reactive zone: the case of strip sources. (14th January 2015) - Solimene, Raffaele; Mola, Claudio; Gennarelli, Gianluca; Soldovieri, Francesco
Abstract: In this work, the singular spectrum of radiation operators is studied for both magnetic and electric sources. The aim is to establish a theory that allow one to foresee the information content of the data as a function of the parameters of the radiation configuration. This is a classical problem and some results have been presented, mainly referring to the far-zone and the Fresnel paraxial zone. Here, we extend the previous studies by considering radiation configurations where no constraints on the source and observation domains are imposed as needed by the far-zone or the Fresnel paraxial zone approximation. However, it is assumed that evanescent waves are negligible. To keep the analysis simple, the case of strip currents is considered within a two-dimensional scalar geometry.